Evaluación de la variabilidad biológica de coliformes y fitoplancton del agua en el humedal La Segua Chone – Manabí - Sánchez Vera, Byron Daniel (2019)
“La Segua” wetland is subject to the RAMSAR agreement whose mission is the conservation and rational use of wetlands through local and national actions and thanks to international cooperation, as a contribution to the achievement of sustainable development throughout the world. With the objective of evaluating the biological variability of Coliforms and Phytoplankton of the water in La Segua Chone - Manabí wetland, period January - April 2019, this non-experimental study used methodologies in which it is established, the assessment of the ecological state of lagoons and wetlands, selecting various sampling points (5 points) in the middle and deep part of the water body for 3 weeks at different times 07H00, 10H00 and 14H00; for the identification of the coliforms, 3M Petrifilm plates were used, and for the identification of the Phytoplankton, it was done by identifying the structure and function of each of the phytoplankton. In the Phytoplankton case, the relationship is maintained in a constant equilibrium despite the presence of discharge of bodies of water from shrimp farms, this made the Cianophytas stand out in high concentrations, which affects the nervous system, causing death to the organism; with regard to biological variability, an Anova was performed to see the degree of significance where it is shown that there is variation between Sampling Points and Schedules, but in the case of depths it has no significance; additionally in the interactions of the three factors they are not related to each other so it is determined that the Biological Variation does not depend on the depth.